Doppler sonographic assessment of endometrial cancer local recurrence in pelvis minor - Czekierdowski, Artur; Chróściel, Mieczysław; Stachowicz, Norbert; Kotarski, Jan (Menopause Review/Przegląd Menopauzalny, 2006)
Objectives: We aimed to characterize vascularization of the suspected masses of vaginal fornix in women after hysterectomy performed because of endometrial cancer. Design: Transvaginal sonography with Doppler blood flow measurements was performed in 38 women operated between 2001-2004 in the Ist Department of Gynecology of the Medical University in Lublin. Material and methods: In all cases presence or absence of central pelvic mass was recorded and - if present - Doppler blood flow indices (PI, RI) as well as peak systolic velocity (PSV) were studied. Clinical data of these patients were recorded and compared between women with and without the central pelvic recurrence of the malignancy. Results: In 21 women with detected masses histologically proven recurrence was found. In 17 women wihout sonographical evidence of the recurrence 10 were operated because of various indications and no microscopic signs of relapse were found. In the remaining 7 non-operated women there were no sonographical signs of central pelvic recurrence during follow-up performed 3, 6 i 12 i 24 months after initial surgery. Mean values of pulsatility and resistive indices were significantly lower in women with the recurrence (p<0,05, Mann-Whitney U test). However, PSV was not a useful additional test of the pelvic mass vascularity. Conclusion: Transvaginal Doppler blood flow indices measurement may be used as an additional test to discriminate suspected central pelvic recurrence of pelvic masses in women previously hysterectomized because of endometrial cancer.